Integrated Environmental Management for Nickel Mining Communities in Papua - Ramandei, Lazarus; Wanane, Yohanis Yulius (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2025)
Nickel mining in Papua has experienced rapid expansion to meet global electric vehicle demand, yet poses significant environmental impacts on local communities. This research aims to develop and evaluate an integrated environmental management model that combines electrocoagulation technology, indigenous knowledge systems, and ecosystem restoration strategies to address wastewater pollution and environmental degradation from nickel mining activities. A mixed-method approach was employed with wastewater quality analysis, ecosystem damage mapping, and indigenous community participation evaluation at three nickel mining sites in Raja Ampat, Southwest Papua. The integrated environmental management approach developed in this study consists of four main components: (1) electrocoagulation wastewater treatment system, (2) community-based environmental management using traditional sasi system, (3) phytoremediation using endemic Papuan plants, and (4) participatory monitoring and evaluation framework. Laboratory-scale electrocoagulation testing showed optimal heavy metal removal efficiency at 1.5 A current intensity, 90-minute contact time, and pH 7.5, achieving 95.2% nickel, 93.8% chromium, and 97.5% iron removal from mining wastewater. Implementation of community-based waste management systems using local wisdom sasi approach reduced environmental degradation by 68% and improved community welfare by 45%. The integrated ecosystem restoration model using endemic Papuan ferns demonstrated 78% effectiveness in soil and water quality recovery within 24 months. The research concludes that integrated environmental management approaches combining sustainable technology, community participation, and indigenous knowledge conservation can provide effective solutions to mitigate negative nickel mining impacts while supporting just clean energy transition.